PELATIHAN MANAJEMEN PEMASARAN DIGITAL BAGI UMKM DI PULAU HARAPAN, KEP. SERIBU, JAKARTA - Dian Ikha Pramayanti; Susbiyantoro; Adine Setya Wardhani; Kurnia; Agus Wibowo (POLITEKNIK LP3I JAKARTA, 2024)
Polytechnic LP3I Jakarta community service activities in collaboration with Pulau Seribu Village, Pulau Harapan. Along with the widespread use of the internet in today's life, every business needs digital marketing. The presence of TikTok adds to the list of social media that have the potential to help promote and develop businesses in Indonesia. Apart from that, using Tiktok social media is not only about posting product photos but also how to package the product content to make it attractive and have bargaining value. The problem that industry players often experience in using Tiktok social media is creating interesting and easy content. In implementing this assistance, the implementation was carried out using the discussion method to map the problems faced by MSMEs in using Tiktok social media. This discussion was used to map the extent of problems in creating TikTok content and using Canva as well as by providing training and mentoring. The activity assistance was attended by around 25 participants from representatives of MSME actors on Harapan Island, Kep Seribu, Jakarta. The final result of this activity is that participants have an overview of using Canva and Tiktok. This activity is also expected to increase partner empowerment, namely the creation of MSMEs that have good knowledge and skills in optimizing digital marketing, especially Canva and Tiktok, in increasing sales. The methods used in this activity are lectures, training and discussions. Overall, the Digital Marketing training activities for UMKM Pulau Harapan, Kep Seribu Jakarta with the theme Canva and Tiktok Optimization went well. It is also hoped that this training can support and help MSME players to improve their ability to use and utilize Digital Marketing Tiktok and Canva to the fullest